Advertisement Remove all ads

Prove that `Cot^2a/(Coseca-1)-1=Coseca` - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Prove that

`cot^2A/(cosecA-1)-1=cosecA`

Advertisement Remove all ads

Solution

`cot^2A/(cosecA-1)-1`

`=(cot^2A-cosecA+1)/(cosecA-1)`

`=(-cosecA+cosec^2A)/(cosecA-1)`

`=(cosecA(cosecA-1))/(cosecA-1)`

= cosecA

Concept: Trigonometric Identities
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Maths Class 10 ICSE
Chapter 21 Trigonometrical Identities
Exercise 21 (E) | Q 10.02 | Page 333
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×